AKTIVITAS ANTIBAKTERI EKSTRAK KULTUR JAMUR ENDOFIT Fusarium sp. CSP-4 YANG DIISOLASI DARI Curcuma sumatrana Miq. - Dewi Wulansari; Ersaliany Nurul Pratiwi Qodrie; Bodhi Dharma; Andi Saptaji Kamal; Lukman Hafid; Lina Marlina; Praptiwi Praptiwi (BERITA BIOLOGI, 2020)
Endophytic fungus Fusarium sp. CSP-4 was isolated from the rhizome of Curcuma sumatrana Miq. The ethyl acetate extract of CSP-4 was fractionated by chromatographic column with silica as a stationary phase. The fractions were tested for antibacterial activity against S.aureus and E.coli by Thin Layer Chromatography (TLC)- bioautography. Determination of Minimum Inhibitory Concentration (MIC) was carried out by the microdilution method on a 96-microwell plate with the concentrations from 2 to 256 µg/ml. The results showed that fraction 15 and 11 were able to inhibit bacterial growth with the MIC values of 256 and> 256 μg / mL against S.aureus and>256 μg / mL against E.coli, respectively.The antibacterial activity of fractions 15 and 11 was weaker compared to the positive control of chloramphenicol with the MIC value of 4 µg/mL against S.aureus and E.coli. Based on the results obtained showed that the fractions of the methanol extract of endophytic fungus Fusarium sp. CSP-4 have weak antibacterial activity.